Organization of the “Court/Judicial Law” in Croatia and EU as a Synthesis of Civil-Commercial and Criminal Law - Radolović, Oliver (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The paper treats the problem of the existence of "court/judicial law" as a unity of civil-commercial and criminal law in Croatia and European Union. The "division" in the legal space of the Republic of Croatia and in the EU member states arose from the past and is basically the result of the specific caracter and ''political preference'' of the criminal justice system. However, the division into civil-commercial and criminal law is maintained in Croatian law and in European Union even now, either by inertia as a habit that is difficult to change, or (most likely) by individual interests within the judiciary and judicature. In a democratic civil society, not political but economic crime prevails, which cannot be followed and understood without knowledge of both civil-commercial and criminal law. Ongoing, mostly too slow and ineffective criminal proceedings in Croatia and EU (many of them in "specialized" courts of justice), fully confirm this thesis.